Fear of hypoglycemia in children with type 1 diabetes and their parents: Effect of pump therapy and continuous glucose monitoring with option of low glucose suspend in the CGM TIME trial. Issue 2 (27th November 2020) - Verbeeten, Kate C; Perez Trejo, Maria Esther; Tang, Ken; Chan, Jason; Courtney, Jennilea M; Bradley, Brenda J; McAssey, Karen; Clarson, Cheril; Kirsch, Susan; Curtis, Jacqueline R; Mahmud, Farid H; Richardson, Christine; et al.
Abstract: To determine if pump therapy with continuous glucose monitoring offering low glucose suspend (LGS) decreases fear of hypoglycemia among children with type 1 diabetes and their parents. The CGM TIME trial is a multicenter randomized controlled trial that enrolled 144 children with type 1 diabetes for at least 1 year (mean duration 3.4 ± 3.1 years) starting pump therapy (MiniMed™ Veo™, Medtronic Canada). CGM (MiniMed™ Enlite™ sensor) offering LGS was introduced simultaneously or delayed for 6 months. Hypoglycemia Fear Scale (HFS) was completed by children ≥10 years old and all parents, at study entry and 12 months later. Simultaneous and Delayed Group participants were combined for all analyses. Subscale scores were compared with paired t‐tests, and individual items with paired Wilcoxon tests. Linear regression examined association with CGM adherence. 121/140 parents and 91/99 children ≥10 years had complete data. Mean Behavior subscale score decreased from 21.1 (SD 5.9) to 17.2 (SD 6.1) ( p < .001) for children, and 20.7 (SD 7.5) to 17.4 (7.4) ( p < .001) for parents. Mean Worry subscale score decreased from 17.9 (SD 11.9) to 11.9 (SD 11.4) ( p < .001) for children, and 23.1 (SD 13.2) to 17.6 (SD 10.4) ( p < .001) for parents. Median scores for 10/25 child items and 12/25 parent items were significantly lower at 12 months ( p < .001). Linear regression found no association between HFS scores and CGM adherence. Insulin pump therapy with CGM offering LGS significantly reduced fear of hypoglycemia not related to CGM adherence in children with type 1 diabetes and their parents.